A bibliometric study on the utilization of lenvatinib in hepatocellular carcinoma (2014-2022) - Cong-Cong Wang; Cai-Yan Yu; Jing Zhang; Rui Wang; Xiang-Shuo Kong (Frontiers Media S.A., 2023)
Background: The REFLECT phase-III trial has demonstrated the efficacy of lenvatinib in improving the overall survival of advanced hepatocellular carcinoma (HCC) patients, comparable to sorafenib. The rapidly evolving landscape of hepatocellular carcinoma therapy presents new avenues for lenvatinib. This study aims to provide a scientometric analysis of publications and predict research hotspots in this field.Methods: Relevant publications were sourced from the Web of Science Core Collection (WoSCC) database up until November 2022. The bibliometrix tool in R was employed for scientometric analysis and visualization.Results: A total of 879 publications from 2014 to 2022 were obtained from WoSCC that met the established criteria. These studies involved 4,675 researchers from 40 countries, with an average annual growth rate of 102.5%. The highest number of publications was from Japan, followed by China, Italy, and the United States. The largest proportion of studies, 14.0% (n = 123), was contributed by FUDAN UNIV. The studies were published in 274 journals, with CANCERS (n = 53) being the top journal, followed by FRONTIERS IN ONCOLOGY (n = 51) and HEPATOLOGY RESEARCH (n = 36). The top ten journals accounted for 31.5% of the 879 studies. The most prolific authors were Kudo M (n = 51), Hiraoka A (n = 43), and Tsuji K (n = 38). A total of 1,333 keywords were analyzed, with the present research hotspots being "immune checkpoint inhibitors," "prognosis," and "pd-1." Co-occurrence clustering analysis revealed the top keywords, authors, publications, and journals. Strong collaboration was identified in the field.Conclusion: This scientometric and visual analysis provides a comprehensive summary of the published articles on lenvatinib in HCC during 2014-2022, highlighting the research hotspots, knowledge domain, and frontiers. The results can provide insights into future research directions in this field.